2020
DOI: 10.1055/a-1200-0199
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic retrograde pancreatography-guided versus endoscopic ultrasound-guided technique for pancreatic duct cannulation in patients with pancreaticojejunostomy stenosis: a systematic literature review

Abstract: Background and aim Stenosis of the pancreaticojejunostomy is a well-known long-term complication of pancreatoduodenectomy. Traditionally, the endoscopic approach consisted of endoscopic retrograde pancreaticography (ERP). Endoscopic ultrasound (EUS)-guided intervention has emerged as an alternative, but the success rate and adverse event rate of both treatment modalities are poorly known. We aimed to compare the outcome data of both interventions Methods We performed a systematic literature search using the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…A recent systematic review compared the outcomes of ERP to EUS-guided PD drainage in patients with pancreaticojejunostomy strictures [109]. This study included 13 studies, in which 77 patients underwent ERP-guided drainage, 145 patients EUSguided drainage, and 12 patients underwent both modalities.…”
Section: How Does Eus-guided Pd Drainage Compare With Erp In Pancreaticojejunostomy?mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review compared the outcomes of ERP to EUS-guided PD drainage in patients with pancreaticojejunostomy strictures [109]. This study included 13 studies, in which 77 patients underwent ERP-guided drainage, 145 patients EUSguided drainage, and 12 patients underwent both modalities.…”
Section: How Does Eus-guided Pd Drainage Compare With Erp In Pancreaticojejunostomy?mentioning
confidence: 99%
“…A recent systematic review (13 studies, 409 patients), showed the overall AE rate of EUS-guided PD drainage to be 15 % [109]. No significant differences were noted with respect to AE rates of EUS-guided PD drainage when comparing patients with native pancreatic anatomy to those with surgically altered pancreatic anatomy (15 % vs. 11 %).…”
Section: Key Question 10: What Are the Most Common Adverse Events Associated With Eus-guided Pd Drainage?mentioning
confidence: 99%
“…Adverse events were not included in their analysis due to the insufficient data. 31 Furthermore, most endoscopes used in previous studies are conventional duodenoscopes or forward viewing scopes. Recently, new short-type therapeutic enteroscopes are commercially available and clinical outcomes of enteroscopeassisted ERCP in patients with surgically altered anatomy have been markedly improved.…”
Section: Comparison With Ercpmentioning
confidence: 99%
“…Transpapillary or transanastomotic PD drainage can be performed by endoscopic retrograde pancreatography (ERP) or balloon-assisted ERP but, for difficult cases, percutaneous or surgical PD drainage is considered [1][2][3]. Recently, endoscopic ultrasound (EUS)-guided PD drainage has been reported, with a high success rate [4].…”
mentioning
confidence: 99%
“…Transpapillary or transanastomotic PD drainage can be performed by endoscopic retrograde pancreatography (ERP) or balloon-assisted ERP but, for difficult cases, percutaneous or surgical PD drainage is considered [1][2][3]. Recently, endoscopic ultrasound (EUS)-guided PD drainage has been reported, with a high success rate [4]. Here, we present the case of a patient with a stenotic pancreaticojejunal anastomosis after pylorus-preserving pancreaticoduodenectomy with the Imanaga reconstruction (PPPD-Imanaga), in which a pancreatic stent was successfully placed using a forward-viewing echoendoscope and diathermic dilator.…”
mentioning
confidence: 99%